2017
DOI: 10.1515/amm-2017-0073
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Angle of the Working Part of the Die on the High Speed Drawing Process of Low Carbon Steel Wires

Abstract: The paper contains the theoretical and experimental analysis of the impact of the drawing angle on the drawing process and the properties of low carbon steel wires. A multi-stage drawing wire rod with a diameter of 5.5 mm on a wire with a diameter of 1.0 mm has been carried out in two stages. The first one consisted of preliminary drawing wire rod for the wire with a diameter of 2.2 mm which was next subjected to the drawing process at a speed of 25 m/sec at the final wire with a diameter of 1.0 mm. The wires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 2 publications
3
17
0
Order By: Relevance
“…The chemical composition in the marked micro-areas is shown in Table 3. The microanalysis of the chemical composition carried out on the surface of the coating from an area of 0.03 mm 2 (Figure 8a, point 1, Table 3) showed the presence of 3.5 wt.% Pb and 96.5 wt.% Fe. The determined Pb content was higher than the Pb content in the bath and significantly exceeded the limit solubility of Pb in Zn in the solid-state.…”
Section: Microstructure (Sem) and Microanalysis (Eds) Of The Coating mentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition in the marked micro-areas is shown in Table 3. The microanalysis of the chemical composition carried out on the surface of the coating from an area of 0.03 mm 2 (Figure 8a, point 1, Table 3) showed the presence of 3.5 wt.% Pb and 96.5 wt.% Fe. The determined Pb content was higher than the Pb content in the bath and significantly exceeded the limit solubility of Pb in Zn in the solid-state.…”
Section: Microstructure (Sem) and Microanalysis (Eds) Of The Coating mentioning
confidence: 99%
“…The durability and reliability of steel structures during their operation in an atmospheric environment depends on the quality of corrosion protection. Zinc coatings obtained by the immersion method are the most effective and economical way to protect steel against corrosion because they provide a barrier and protective protection of the substrate [1], high resistance to mechanical loads [2], and above all, unlike paint coatings, they do not require any renovation and expensive repairs during operation.…”
Section: Introductionmentioning
confidence: 99%
“…To alleviate the undesired effects, a lubricant is usually utilized [12]. The tribological problems concerning the wire drawing process have been studied both experimentally [13][14][15] and theoretically [6,[16][17][18][19][20][21][22]. In particular, numerical analyses, such as the finite element method, have been extensively employed in previous researches [6,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Suliga [22] showed that the geometry of the reduction zone, for instance, the die angle 2β, influences the temperature in the top layer of the wire considerably. The decrease in the die angle implies an increase of the wire/die contact length.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of die drawing in the metalworking processes has attracted much attention. A vital feature of the process is that the resulting stress is applied indirectly by an external source, as in the cases of extrusion [1,2] and wire drawing [3]. Previous studies on wire drawing have reported the improvement of the drawing quality by selecting the appropriate die geometry (Figure 1).…”
Section: Introductionmentioning
confidence: 99%